Effect of temperature on fatty acid composition of unfed Siberian sturgeon (A. baerii) larvae - M. Vasconi; L. Aidos; A. Di Giancamillo; F. Bellagamba; C. Domeneghini; V. M. Moretti (2017)
The fatty acid metabolism in fish is influenced by various factors, including fish species, water temperature, water environment and diet supply. The aim of present work is to investigate the fatty acid composition of yolk-stage Siberian sturgeon larvae reared at three different temperatures. Fertilized Siberian sturgeon eggs were transferred to the Lodi Aquaculture Research Center of the University of Milan, divided in three aquaria, containing each three net cages and incubated at 16°C. After hatching the temperature has been switched to 16, 19 and 22 °C. Larvae sampling was performed at the end of yolk sack reabsorption. No feed was dispensed during the trial. Eggs and larvae were weighted and fatty acid profile was determined by GC-FID analysis after lipid extraction by chloroform/methanol mixture and fatty acid transesterification by methanolic hydrogen chloride. The fertilized eggs presented a weight of 23.27 mg and a lipid content of 2.67 mg/egg. At hatching, the weight was 12.2 mg and lipid content 1.9±0.6 mg/larva. At the end of the trial, larvae mean weight was 33.6±3.6, 34.7±1.8 and 36.9±1.1 mg, while lipid content was 2.0±0.3, 2.1±0.3 and 2.0 ±0.2 mg for larvae reared at 16, 19 and 22°c respectively, without statistically significant difference. The fatty acid composition of larvae has been affected by the temperature. Larvae reared at 16°C presented a lower amount of saturated fatty acids, due to a low palmitic acid content, offset by a higher level of linolenic and linoleic acid, if compared with larvae reared at 19°C and 22°C. The study suggests that at a lower temperature sturgeon spare unsaturated fatty acid consuming preferably saturated fatty acids, increasing our knowledge of the fatty acid metabolism in this species.